2022
DOI: 10.2147/idr.s374265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prevalence of Side-Effects Associated with Booster Dose of mRNA-Based COVID-19 Vaccine Among Healthcare Workers in Eastern Province, Saudi Arabia: A Descriptive Cross-Sectional Study

Abstract: Background The purpose of this study was to examine the mild and moderate side‐effects experienced by the healthcare workers (HCWs) in the Eastern Province of Saudi Arabia after receiving the booster dose of the Pfizer-BioNTech/BNT162b2 COVID‐19 vaccine. Methods We directed a descriptive cross-sectional study among adults living in the Eastern Province of Saudi Arabia. A survey link was distributed through WhatsApp, SMS, or e-mail to HCWs. Participants’ general and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…Our study showed that the most frequent adverse effects were pain at the injection site, fatigue, muscle pain, swelling at the injection site, headache, fever and chills. These findings are in accordance with the literature regarding the adverse effects of the first booster dose [1418,22,23]. Moreover, a recent systematic review investigated the prevalence of adverse effects after the primary COVID-19 vaccine doses and found that the most frequent adverse effects among 10,632 participants were pain at the injection site (77.3%), muscle pain (39.7%), swelling at the injection site (34%), headache (33.3%), chills (18.3%), fever (18%), swollen lymph nodes (8%), nausea (7.9%), and shortness of breath (7.6%) [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that the most frequent adverse effects were pain at the injection site, fatigue, muscle pain, swelling at the injection site, headache, fever and chills. These findings are in accordance with the literature regarding the adverse effects of the first booster dose [1418,22,23]. Moreover, a recent systematic review investigated the prevalence of adverse effects after the primary COVID-19 vaccine doses and found that the most frequent adverse effects among 10,632 participants were pain at the injection site (77.3%), muscle pain (39.7%), swelling at the injection site (34%), headache (33.3%), chills (18.3%), fever (18%), swollen lymph nodes (8%), nausea (7.9%), and shortness of breath (7.6%) [11].…”
Section: Discussionsupporting
confidence: 93%
“…Literature supports this finding since two other studies found that all participants had adverse effects after the first booster dose [20,21]. Other studies found also high prevalence of adverse effect after the first booster dose ranging from 74.7% to 89% [14][15][16][17]22,23]. Slight differences in prevalence of adverse effects among studies could be attributed to different study designs, populations, and definitions.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 79%
“…In fact, describing the side effects of booster vaccines could help to confirm the safety of these vaccines and, therefore, help to reduce the phenomenon of vaccine (booster) hesitancy, which is a phenomenon described for both primer and booster doses of COVID-19 in Algeria [26,29] and around the world [30,31]. Only limited data are available around the world about the side effects of boosters [16,20,[32][33][34][35][36]. Moreover, little is known about the frequency of these side effects in Algeria.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Slovakia among health workers did not differ much from what was mentioned in previous studies, where the side effects of the vaccine were injection site pain (85.2%), fatigue (54.2%), headache (34.3%), muscle pain (28.4%), and chills (26.4%) [16]. Several studies around the world nd that muscle pain in injection sites is the most prevalent side effect symptom of vaccines [17][18][19][20][21][22]. The study conducted by Zare in Iran [23] revealed that Pain and tenderness at the injection site, fever, and muscle pain are the most common side effect and this coincides with all the studies around the world that have been conducted so far among healthcare staff, which con rmed that the vaccine is safe and has no serious side effects.…”
Section: Discussionmentioning
confidence: 96%